Gambling regulation and vulnerability - Carran, Malgorzata Anna (Elgar studies in law and regulation, 2018)
Since the UK Gambling Act of 2005 was introduced, gambling has stopped being seen, politically and legally as an inherent vice and is now viewed as a legitimate form of entertainment. Gambling Regulation and Vulnerability explores the laws around gambling that aim to protect society and individuals, examining the differences between regulatory rhetoric and the impact of legislative and regulatory measures. Malgorzata Carran finds that although the Gambling Act introduced many positive changes to gambling regulation, it has created an environment in which protection of vulnerable individuals becomes difficult. Carran challenges the existing legislative premise that regulation alone is able to balance the effect of liberalisation for those who are vulnerable. Uniquely, this book's findings are underpinned by empirical data from focus groups carried out with children and young people in secondary schools. The young people interviewed have experienced the transition from a contained, to liberalised gambling industry and unless there is a reversal in policy, no comparable empirical data is ever likely to be collected. This title will appeal to academics exploring regulation, sociology, and law and society. Similarly, regulators and those working with the gambling industry will find this an insightful and illuminating text.